2008
DOI: 10.1007/s10388-008-0155-y
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal leiomyosarcoma: a case treated by endoscopic resection

Abstract: We report a rare case of leiomyosarcoma of the lower esophagus that was treated by endoscopic resection. A 56-year-old man was referred to our hospital in October 2005 because of mild discomfort around the lower esophagus upon swallowing for 2 months. The esophagogram showed a fi lling defect at the lower esophagus. It revealed a giant polyp tumor arising from the right wall of the lower esophagus. The diameter of the top of the tumor was 25 mm. Upper gastrointestinal endoscopic study revealed that the lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In addition to the abovementioned epithelial-derived esophageal malignancies, mesenchymal malignancies can occur in the esophagus. Tatsushi et al [ 17 ] first reported an intraluminal polypoid form of esophageal leiomyosarcoma treated with endoscopic resection with an electric snare in 2008. Yamamoto et al [ 18 ] performed en bloc resection by ESD for the therapeutic diagnosis of leiomyosarcoma in cases where several biopsy specimens could not confirm the pathology results and the tumor had rapidly grown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the abovementioned epithelial-derived esophageal malignancies, mesenchymal malignancies can occur in the esophagus. Tatsushi et al [ 17 ] first reported an intraluminal polypoid form of esophageal leiomyosarcoma treated with endoscopic resection with an electric snare in 2008. Yamamoto et al [ 18 ] performed en bloc resection by ESD for the therapeutic diagnosis of leiomyosarcoma in cases where several biopsy specimens could not confirm the pathology results and the tumor had rapidly grown.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, thoracoscopic mobilization for leiomyosarcoma of the esophagus has not been described in literature. Apart from a mention of two minimally invasive approaches without details in a case series of esophageal sarcomas in general 3 and isolated endoscopic and local resections for small polypoidal variants, 4 5 the vast majority of esophageal leiomyosarcomas have been resected through the open approach. 6 7 8 9 10 The reason probably is the fact that these tumors have been known to attain sizes as large as 16 cm in length and present as mediastinal masses with deep ulcerations.…”
Section: Discussionmentioning
confidence: 99%
“…Suwa et al . first reported a case of intraluminal polypoid leiomyosarcoma treated without any trouble by endoscopic resection using an electric snare . Polypoid type, early stage, and good differentiation of esophageal leiomyosarcomas have been shown to represent favorable prognostic factors, so endoscopic resection may be a useful choice for polypoid‐type leiomyosarcoma with no metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcomas usually show slow growth and late metastasis, and carry a good prognosis . Treatment mostly involves surgical excision, so few cases with endoscopic resection have been described . Herein, we report a case of polypoid leiomyosarcoma of the esophagus treated by endoscopic submucosal dissection (ESD), representing the first report of ESD to treat this disease.…”
Section: Introductionmentioning
confidence: 99%